Scientific Approach-Based English Learning Strategy in Online Learning: Learners’ Satisfaction and Obstacles - David Berthony Manalu; Selviana Napitupulu (Master Program in Linguistics, Diponegoro University, 2022)
This research investigated the application of Scientific Approach-Based English Learning Strategy (SABELS) in online learning for higher education level. Twenty items of closed-ended questionnaire were designed to indicate learners’ satisfaction and one item of open-ended questionnaire was to list some obstacles during online learning. The sample of this research was 215 learners who contracted Curriculum and Material Development (CMD) course in the fifth semester. It was found that the respondents were very satisfied towards the application of this strategy in online course. Some problems encountered by learners were unstable internet network, frequent power outage, slow response by lecturer in chatting, time consumption during online team work, and lack of motivation in self-learning. In conclusion, this new strategy has encouraged learners to do collaborative, research-based, and character building-based learning. Further study is suggested especially on investigating its effectiveness through experimental research.